(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Network segmentation is a critical cybersecurity strategy that involves dividing a network into smaller, isolated segments or subnetworks to enhance security and improve network performance. By limiting access to sensitive data and systems, network segmentation reduces the attack surface and prevents lateralmovement by malicious actors within an enterprise network. This research article examines the role of network segmentation as a defense mechanism in securing enterprise networks. It explores the methodologies, benefits, and challenges associated with implementing network segmentation. The study employs a mixed-methods approach, including a comprehensive literature review and analysis of real-world case studies, to assess the effectiveness of network segmentation in mitigating cyber threats. The findings highlight that while network segmentation significantly enhances security posture by containing breaches and restricting unauthorized access, it also presents challenges such as increased complexity and management overhead. The paper concludes with recommendations for best practices in implementing network segmentation to bolster enterprise security